-3w+3=-2w-8

Simple and best practice solution for -3w+3=-2w-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3w+3=-2w-8 equation:


w in (-oo:+oo)

3-3*w = -2*w-8 // + -2*w-8

3-3*w-(-2*w)+8 = 0

2*w-3*w+3+8 = 0

11-w = 0 // - 11

-w = -11 // * -1

w = 11

w = 11

See similar equations:

| 2x^2a(8x^5a-4+5x^2a+1)=16x^31+10x^21 | | 9+3x=-3x+15 | | 6b+7=2b-1 | | 5x+13=62-10x | | -a+6=a+6 | | -1x/4+4=3x/4+8 | | -t+1=6t+50 | | 7-4n=4n-41 | | 2n-8=5n-2 | | 7a+2=a+2 | | m+10=-20-2m | | -2+7m=-5m+82 | | 2x-6/3=x+7 | | 9-2x=-5x+30 | | -3-6t=7t-16 | | 3+5w=7w-5 | | w+4=7w-26 | | 6n+5=-3n+50 | | 3a-1=2a+2 | | 3m+5=6m-25 | | 9+5=-9+7x | | 4w-5=2w-15 | | 1-6w=4w+71 | | -7-4a=a+13 | | 7w-2=-6w-41 | | 6w+4=w+24 | | m+2=0-m | | h/3=9 | | x(3x+7)=0 | | -6t+2=-6+2t | | -8-2w=-4w+14 | | -2n+4=7n-77 |

Equations solver categories